Cryo-EM structures of amyloid-β filaments with the Arctic mutation (E22G) from human and mouse brains - Yang, Yang; Zhang, Wenjuan; Murzin, Alexey G.; Schweighauser, Manuel; Huang, Melissa; Lövestam, Sofia; Peak-Chew, Sew Y.; Saito, Takashi; Saido, Takaomi C.; Macdonald, Jennifer; Lavenir, Isabelle; Ghetti, Bernardino; et al. (Acta neuropathologica, 2023)
The Arctic mutation, encoding E693G in the amyloid precursor protein (APP) gene [E22G in amyloid-β (Aβ)], causes dominantly inherited Alzheimer’s disease. Here, we report the high-resolution cryo-EM structures of Aβ filaments from the frontal cortex of a previously described case ( A β PParc1 ) with the Arctic mutation. Most filaments consist of two pairs of non-identical protofilaments that comprise residues V12–V40 (human Arctic fold A) and E11–G37 (human Arctic fold B). They have a substructure (residues F20–G37) in common with the folds of type I and type II Aβ42. When compared to the structures of wild-type Aβ42 filaments, there are subtle conformational changes in the human Arctic folds, because of the lack of a side chain at G22, which may strengthen hydrogen bonding between mutant Aβ molecules and promote filament formation. A minority of Aβ42 filaments of type II was also present, as were tau paired helical filaments. In addition, we report the cryo-EM structures of Aβ filaments with the Arctic mutation from mouse knock-in line App NL−G−F . Most filaments are made of two identical mutant protofilaments that extend from D1 to G37 ( App NL−G−F murine Arctic fold). In a minority of filaments, two dimeric folds pack against each other in an anti-parallel fashion. The App NL−G−F murine Arctic fold differs from the human Arctic folds, but shares some substructure.